1985
DOI: 10.2113/gsecongeo.80.1.148
|View full text |Cite
|
Sign up to set email alerts
|

Aluminous granite as a source magma of hydrothermal ore deposits; an experimental study

Abstract: Partition ratios of zinc and lead between synthetic granitic melts and aqueous phase were determined at 800øC and under PH•o = 3.5 _ 0.25 kb. Two starting glasses in the system SiO2-A12Oa-CaO-Na20 were prepared. Their bulk chemical compositions are similar, i.e., SiO2 content of 75.65 percent in glass 1 and of 74.68 percent in glass 2. Glass 1 is prepared to be slightly alkaline with 1.89 percent normative wollastonite and glass 2 is slightly aluminous with 2.42 percent normative corundum. The partition ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(31 citation statements)
references
References 9 publications
1
28
1
1
Order By: Relevance
“…Thus the chlorine content of the fluid phase may be critical to the REE contents of the magmatic fluid, as is like to other major, trace, and ore elements in hydrothermal fluids (e.g., Burnham, 1967;Holland, 1972;Urabe, 1985;Webster et al, 1989). The strong influence of pressure on K Cl (wt% Cl in fluid / wt% Cl in granitic melt) is well established for granitic systems (e.g., Kilinc and Burnham, 1972;Shinohara et al, 1989;Webster, 1992a).…”
Section: Sample/chondritementioning
confidence: 98%
See 1 more Smart Citation
“…Thus the chlorine content of the fluid phase may be critical to the REE contents of the magmatic fluid, as is like to other major, trace, and ore elements in hydrothermal fluids (e.g., Burnham, 1967;Holland, 1972;Urabe, 1985;Webster et al, 1989). The strong influence of pressure on K Cl (wt% Cl in fluid / wt% Cl in granitic melt) is well established for granitic systems (e.g., Kilinc and Burnham, 1972;Shinohara et al, 1989;Webster, 1992a).…”
Section: Sample/chondritementioning
confidence: 98%
“…Therefore it is assured that various conditions in granitic system decide the chlorine content in the hydrothermal fluid released from the granitoids, and in turn the chlorine content has a significant effect on the absolute content of REEs in the fluid. However, it is generally considered that magmatic fluids responsible for base metal ore deposits had relatively high chlorine contents (Holland, 1972;Urabe, 1985). Such magmatic fluids with high chlorine contents are expected to have general features including no Ce anomaly, a positive Eu anomaly, and a high (La/Yb) cn ratio, while absolute REE abundances may differ considerably.…”
Section: Sample/chondritementioning
confidence: 99%
“…./ Previous investigations on trace-element distribution have shown that melt polymerization (expressed as the number of non-bridging oxygen per tetrahedral cation (NBO/T)) has a distinct effect on the partitioning behavior of trace elements, including ore metals (Urabe, 1985;Lowenstern et al, 1993;Kohn and Schofield, 1994;Tang, 2003). The increase of alkali as network-modifiers in silicate melt can lead to an increase in the concentrations of NBO atoms and a decrease in the degree of melt polymerization (Jiang et al, 2003).…”
Section: Effects Of Melt Composition On D Snmentioning
confidence: 99%
“…Many experimental studies have indicated that the formation of ores associated with magmatic rocks depends, to a great extent, on partitioning of metal elements between melt and fluid, which depends on the composition of melt, the composition of fluid derived from the melt and the physicochemical conditions under which the partitioning occurs (Holland, 1972;Feiss, 1978;Candela and Holland, 1984;Urabe, 1985;Candela, 1989;Keppler and Wyllie, 1991;Lowenstern et al, 1991;Peiffert et al, 1994;Candela and Piccoli, 1995;Chantal et al, 1996;Webster, 1992aWebster, , 1997Bai et al, 1998;Halter et al, 2002). Some experimental studies have revealed that different melts have distinct effects on the partitioning of Cu, Pb, Zn, U between melt and coexisting aqueous fluid (Chantal et al, 1996;Bai et al, 1998;Tang, 2003).…”
mentioning
confidence: 99%
“…The peraluminous property of phase III granites is favourable for the partitioning of oreforming elements into hydrothermal fluids. The experimental data by Urabe (1985) reveal that the partition ratio of Zn (Znfi u id/Zn me lt) for aluminous melt (CIPW normative corundum is 2.42 %) is more than two orders of magnitude larger than that for the alkaline melt (CIPW normative corundum is 0 %), and a similar contrast was observed for the partition ratio of Pb. From his experiments he concluded that only aluminous granite is capable of producing hydrothermal fluids which contain a significant amount of ore metals while alkaline melt tends to retain these metals instead of releasing them into the hydrothermal fluids.…”
Section: The Ore-forming Potentialmentioning
confidence: 76%